Relevant Words Extraction Method in Text Mining - Naw Naw (Bulletin of Electrical Engineering and Informatics, 2013)
Nowadays, E-commerce is very popular because of information explosion. Text mining is also important for information extraction.  Users are more preferable to use the convenience system from many sources such as through web pages, email, social network and so on. This system proposed the relevant words extraction method for car recommendation system from user email. In relevant words extraction, this system proposed the Rule-based Technique based on Compiling Technique. Context- free grammar is very suitable for relevant words extraction. The extracted keys will be used in recommendation system. Recommendation System (RS) is a most popular tool that helps users to recommend according to their interests. In recommendation, this system proposed Content-based Filtering approach with Jaccard Coefficient that will help the users who want to buy the car by providing relevant car information.